Valuasi Potensi Ekonomi Obyek Wisata Laut Olele dan Strategi Pengembangan Ekonomi Daerah - Sri Aryanti; Sri Endang Saleh; Boby Rantow Payu (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2020)
This research was aimed at finding out the economic valuation in Olele Marine Park and determining development strategy for the tourist attraction as effort to improve the regional economic. Research data were retrieved from Tourism Agency of Gorontalo Province, Tourism Agency of Bone Blolango District, ans questionnaire distributed to method and Strength Opportunity Threats (SWOT) strategy analysis. Finding of research revealed that the economic value created through involvement of tourist visit in the Olele Marine Park based on respondents’ average of willingness to pay (WTP) was IDR 732.828/person, and the cost has covered accommodation, transportation, meal, and snorkeling and diving equipment. The value was believed to be increasing time by time as more tourists were attracted to visit the spot